Keunikan Suku di Indonesia dalam Mempersatukan Bangsa ditengah Perbedaan Budaya - Djenap Zamilummi Polhaupessy; Edy Soesanto; Nazwa Maharani (Pusat Riset dan Inovasi Nasional, 2025)
Ethnic and cultural diversity is not only a characteristic of Indonesia, but also part of national identity. Indonesia is known as a country with extraordinary tribes and cultures. Consisting of more than 300 ethnic groups and 700 regional languages. Indonesia is a clear example of the motto